Can necrotizing soft tissue infection be reliably diagnosed in the emergency department?. Issue 1 (13th January 2018) - Henry, Sharon M; Davis, Kimberly A; Morrison, Jonathan J; Scalea, Thomas M
Abstract : Necrotizing soft tissue infections (NSTIs) are associated with a high mortality and require prompt recognition and treatment, consisting of aggressive surgical debridement and critical care support. Diagnosis is a key step, which is generally made in the operating room (OR), but the decision to debride requires guidance. This is frequently made on clinical grounds, but NSTI can be occult in presentation and several other infective processes can mimic NSTI. It is unknown whether the various scoring systems described in the literature can enable clinicians to reliably diagnose NSTI in the emergency department, rather than the OR. The topic was debated at the 36thAnnual Point/Counterpoint Acute Care Surgery Conference and the following article summarizes the discussants points of view along with a summary of the evidence. Level of evidence: Level III.